Lexical Translanguaging in Textbook Preparation for Education in the Gamo Language of Ethiopia - Gelagay, Almaz Wasse (Languages (Basel), 2023)
As a country where more than 85 languages are spoken, Ethiopia framed, in its Education and Training Policy of 1994, which was revised in 2021, the right to use mother tongue in primary education. Following this, around 33 languages are implemented in schools as a Medium of Instruction (MoI). Gamo is one of the languages used as a MoI in primary education and taught as a subject up to high school. This functional expansion of Gamo into Education required textbook preparation, and accordingly, textbooks for different subjects, including Gamo as a language subject, were published. One major feature of the Gamo textbooks is availability of Amharic and English words, and this research aims to apply translanguaging, which is the discursive language practices of bilingual speakers to describe the practice of using words from different languages in the textbooks. Lexical data were collected from five textbooks written in Gamo and interviews were held with students and teachers to find out information about the process of textbook writing and translanguaging. The strategies identified in the textbooks include alternative translanguaging, borrowing, lexical inventions and bilingual compounds. These strategies were used to address education in the Gamo language and to communicate meaning effectively. Writers used their Amharic and English repertoire to represent meaning when a word for a concept is not available in Gamo. In other instances, alternative words were provided as a means of enhancing meaning clarity.